2001
DOI: 10.1002/ffj.1047
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of leaf and flower essential oil of Lantana camara from India

Abstract: The chemical composition of leaves and flowers essential oils of Lantana camara from India were analysed by GC and GC-MS, which resulted in the identification of 71 and 64 constituents, representing 99.0% and 97.0% of the oils, respectively. The major constituents in the leaf oil were germacrene-D (20.5%), -elemene (10.3%),ˇ-caryophyllene (9.4%),ˇ-elemene (7.3%),˛-copaene (5.0%) and˛-cadinene (3.3%), while the major constituents in the flower oil wereˇ-elemene (14.5%), germacrene-D (10.6%),˛-copaene (10.7%),˛-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 7 publications
1
34
0
1
Order By: Relevance
“…The germacrene-D was present in some EOLC analyzed (Sundufu & Shoushan, 2003;Da Silva et al, 1999;Khan et al, 2002) and the cariophylene groups were observed to be the only versatile components present in every EOLC analyzed by different authors (Ngassoum et al, 1999;Sefidkon, 2002;Rana, 2005), which is confirmed by the present work.…”
Section: Resultssupporting
confidence: 88%
“…The germacrene-D was present in some EOLC analyzed (Sundufu & Shoushan, 2003;Da Silva et al, 1999;Khan et al, 2002) and the cariophylene groups were observed to be the only versatile components present in every EOLC analyzed by different authors (Ngassoum et al, 1999;Sefidkon, 2002;Rana, 2005), which is confirmed by the present work.…”
Section: Resultssupporting
confidence: 88%
“…The chemical composition of the essential oil of Iranian L. camara described in this study agreed quite well with those previously reported in the literature; however, there were differences in relative quantities of volatile compounds. Among the main compounds, sabinene (Sefidkon, 2002;Saikia and Sahoo, 2011), germacrene-D (Khan et al, 2002), bicyclogermacrene (Sefidkon, 2002;Saikia and Sahoo, 2011), zingeberene (Kruade et al, 2010) and caryophyllene oxide (Zoubiri and Baaliouamer, 2011) have been reported from essential oils of L. camara leaves in other studies. Differences in quality and quantity of essential oil composition among this study and others may be due to genetic, climate, geographical, and seasonal variations.…”
Section: Chemical Compounds Of Essential Oilmentioning
confidence: 88%
“…The essential oil from flowers of L. camara provided 0.30% yield (Table 1), a yield lower than that obtained for an Iranian sample, 0.63% (Sefidkon, 2002), but was higher than that obtained for an India species, 0.08% (Khan et al, 2002). GC-FID and GC-MS analyses of the essential oil of L. camara showed presence of 20 compounds, accounting for 82% of the total components ( Figure 1, Table 1).…”
Section: Resultsmentioning
confidence: 89%
“…For instance, in the oil obtained from a L. camara voucher collected in India (Khan et al, 2002), the major compounds identified were β-elemene (14.5%), germacrene D (10.6%), α-copaene (10.7%), α-cadinene (7.2%), β-caryophyllene (7.0%) and γ-elemene (6.8%); on the other hand, the essential oil obtained from L. camara flowers grown in Iran showed sabinene (16.5%), β-caryophyllene (14.0%), 1,8-cineole (10.0%), bicyclogermacrene (8.1%) and α-humulene (6.0%) as major compounds (Sefidkon, 2002). El Baroty et al (2014) report the essential oil chemical composition of L. camara flowers obtained in Cairo, Egypt, where the majority chemicals differ from those presented in Table 1 among other differences.…”
Section: Resultsmentioning
confidence: 99%